CAPITAL IN WORKERS' SURVIVAL STRATEGIES UMKM KERUPUK KOMPLANG IN BENGKULU CITY - Fitri Ratna Sari; Susiyanto Susiyanto; Lesti Heriyanti (Jurnal Analisa Sosiologi, 2025)
This study aims to examine the survival strategies employed by MSME workers in the kerupuk komplang sector of Bengkulu City. This sector serves not only as a local culinary provider, but also as a significant source of income for the community. However, businesses and workers face several challenges, including changes in income, rising raw material costs, limited funds, and dependence on the local market. This research employs a qualitative approach, utilising the case study method. Data were collected through various means, including observation, document collection, and in-depth interviews with five key informant workers, business owners, and family members who are directly involved in the komplang cracker production process. The findings of this study reveal that MSME workers implement various ways to survive, both economically and socially. Techniques include job variation, austerity, saving even small amounts of money, and leveraging social networks for informal support, such as interest-free loans or labour assistance. Social capital is a crucial element in enhancing workers' resilience. In this context, Robert D. Putnam's theory of social capital is highly relevant, given the importance of networks, norms, and trust in fostering mutually beneficial social cooperation. Social capital is evident in the form of community solidarity, mutual trust between individuals, and the exchange of resources within family environments and the workplace. Even in times of crisis, social capital serves as a major lifeline. From a theoretical point of view, social workers face economic labour.